Review paperSkin tests with native alimentary allergens in the diagnostics of food allergy - Rosińska-Więckowicz, Anna; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Despite continuous progress in the field of medical sciences, diagnostics of food allergy remains a difficult issue. First of all in order to diagnose food allergy specific elimination diet should be applied to the patient and accurate clinical examination followed by various diagnostic tests should be performed in order to exclude more probable causes of symptoms observed and decrease the risk of unnecessary, strict elimination diets. Double blind placebo controlled food challenge (DBPCFC) remains a golden standard in the diagnostics of food allergy. In cases when DBPCFC is difficult to perform, tests with native food allergens, such as atopy patch test (APT), skin application food test (SAFT) or prick-by-prick tests are very helpful diagnostic tools. The right choice of test depends on the type of symptoms observed in patients: SAFT and prick-by-prick tests are used if immediate while APT if late reactions after ingestion of food are suspected. Furthermore, SAFT is an alternative to SPT in children younger than 3 years and in this group of patients it is even considered as a skin provocation test. The proper choice APT shows very high sensitivity and specificity, according to late phase reactions (> 90%), which are comparable with those of DBPCFC.